5 Current NHS service provision for CT coronary angiography and forecasts of requirements following nice CG95 2016. (18th May 2017) - Dreisbach, John; Nicol, Edward; Roditi, Giles
Abstract : Introduction: The updated NICE guidelines 'chest pain of recent onset: assessment and diagnosis' (CG95) recommend CT Coronary Angiography (CTCA) as the first line investigation for stable chest pain if clinical assessment indicates typical or atypical angina, or non-anginal chest pain with ECG changes suggesting underlying coronary artery disease. The aim of our investigation was to assess the current provision of CTCA within the NHS, estimate the requirement if the guidelines are fully implemented, and identify geographic variation in delivery. Ancillary aims were to survey the number of CTCA-capable scanners and formally accredited CTCA practitioners. Methods: The annual number of CTCA scans performed was surveyed across the NHS. Potential requirement for CTCA was estimated by applying the number of percutaneous coronary interventions (PCI) performed for stable chest pain in 2014 (31, 727 according to the National Audit of PCI Annual Report) to the ratio of CTCA: revascularisation (1778:233) observed in SCOT-HEART (7.6:1). Registries of CTCA-capable scanners were obtained from manufacturers and formally accredited practitioners from the BSCI/BSCCT and SCCT. Results: 42, 340 CTCAs are currently performed annual and we estimate 350, 000 would be required to fully implement the guidelines. 302 CTCA-capable scanners and 198 formally accredited practitioners were identified. Marked geographic variation between health regions was observed. Conclusion: This study provides insight into the scale of increases in the provision of CTCA required to fully implement updated NICE guidelines. The currently small specialist workforce and limited number of CTCA-capable scanners may present significant challenges to the expansion of services.